Serum Plant Sterols Associate with Gallstone Disease Independent of Weight Loss and Non-Alcoholic Fatty Liver Disease - Käkelä, Pirjo; Männistö, Ville; Ilves, Imre; Vaittinen, Maija; Tauriainen, Milla-Maria; Eskelinen, Matti; Gylling, Helena; Paajanen, Hannu; Pihlajamäki, Jussi (Obesity surgery, 2017)
Background Gallstone disease (GD) has been associated with low serum levels of plant sterols. We evaluated the impact of laparoscopic Roux-en-Y gastric bypass (LRYGB) and non-alcoholic fatty liver disease (NAFLD) on the association of GD with low levels of serum plant sterols. Methods Two hundred forty-two consecutive morbidly obese patients were recruited to this prospective study. Histological analysis of liver biopsy to diagnose NAFLD was performed. Bile sample was taken during the LRYGB. Associations of GD with serum non-cholesterol sterol to cholesterol ratios, measured using gas liquid chromatography and with mRNA expression of genes participating in the cholesterol, bile, and fatty acid metabolism in the liver, were analyzed. Results Out of the 242 participants, 95 had GD. Lower weight ( p = 0.002) and female sex ( p